The influence of career decision-making self-efficacy on employability of higher vocational students: mediated by emotional intelligence - Zhou, Daleng; Peng, Zeyi; Zhou, Hongling (Frontiers in Education, 2023)
This study explored the relationship between career decision-making self-efficacy, employability, and emotional intelligence among senior vocational students in Guangdong, Hong Kong, and Macau Bay Area. A questionnaire was surveyed to 1078 senior vocational students, the results showed that: career decision-making self-efficacy of senior vocational students had a significant positive effect on employability; emotional intelligence of senior vocational students had a significant positive effect on employability; career decision-making self-efficacy of senior vocational students had a significant positive effect on emotional intelligence; Emotional intelligence of senior vocational students mediates the relationship between career decision-making self-efficacy and employability.